Investigation of chemical constituents, antioxidant, anti-inflammatory and nutritional properties of oil of Persea americana (Avocado) seeds - Uchechi Bliss Onyedikachi; Chukwuebuka Callistus Nkwocha; Emmanuel Ejiofor; Chukwu Charles Nnanna (Food Chemistry Advances)
This study investigated the phytochemical composition, in vitro antioxidant, and anti-inflammatory properties of the oil of Persea americana seeds (OPAS). The flavonoid and total phenol compositions were quantified using standard colorimetric methods; the antioxidant potentials of the seed were determined using 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays, while the anti-inflammatory potentials were investigated using membrane stabilization (hypotonicity) and heat-induced hemolysis of human red blood cells (HRBC) assays. In addition, gas chromatography-mass spectrometry (GC–MS) analysis was employed to characterize the phytochemicals in the oil. The nutritional indices (atherogenic index, thrombogenic index, and polyene index) were also calculated. Results indicated high total phenolic and flavonoid contents (25.78 ± 0.68 mg gallic acid equivalent per gram (GAE/g) and 72.69 ± 1.11 mg quercetin equivalent per 100 mg (QE/100 mg), respectively). The oil of P. americana seeds showed dose-dependent (25–400 μg/mL) antioxidant and anti-inflammatory activities compared to the standard agents used (olive oil and ascorbic acid). The GC–MS analysis showed the presence of fatty acids including tetradecanoic acid (33.33 %), 9, 12-octadecadienoic acid, methyl ester (20.12 %), n-hexadecenoic acid (7.07 %), and oleic acid (11.60 %). Nutritional indices showed that OPAS had a very low polyunsaturated/saturated (PUFA/SFA) ratio (0.45), hypocholesterolemic/hypercholesterolemic (0.26), but high atherogenicity index (IA) (4.13) and thrombogenicity index IT (9.47) values. The beneficial potentials of OPAS revealed in this study suggest that it can be harnessed as a potent antioxidant and anti-inflammatory agent in phytomedicine. However, the nutritional quality and culinary suitability of OPAS with different oils require further study.